1982
DOI: 10.1007/bf00028304
|View full text |Cite
|
Sign up to set email alerts
|

Compositional stability of an oat multiline

Abstract: Mixtures of genotypes are frequently unstable in composition when propagated over successive generations . This study was designed to test whether a multiline cultivar of oats (Avena sativa L .) created to control crown rust disease (caused by Puccinia coronata CDA .) would reflect differential near-isogenic line survivals when propagated under conditions of either presence or absence of rust . An oat multiline cultivar synthesized from near-isogenic lines that had different genes for resistance to crown rust … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

1985
1985
2013
2013

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 31 publications
0
4
1
Order By: Relevance
“…The initial and harvested proportions of the cultivars changed only little, indicating that competitive interactions among the three cultivars were similar. This is in contrast to other studies with barley (Harlan & Martini, 1938;Blijenburg & Sneep, 1975), oats (Murphy et al, 1982), and wheat (Finckh & Mundt, 1992a), where initial and harvested frequencies usually varied greatly.…”
Section: Disease and Yield In Barley Mixtures 811contrasting
confidence: 88%
“…The initial and harvested proportions of the cultivars changed only little, indicating that competitive interactions among the three cultivars were similar. This is in contrast to other studies with barley (Harlan & Martini, 1938;Blijenburg & Sneep, 1975), oats (Murphy et al, 1982), and wheat (Finckh & Mundt, 1992a), where initial and harvested frequencies usually varied greatly.…”
Section: Disease and Yield In Barley Mixtures 811contrasting
confidence: 88%
“…The first is the effect of plant-plant interactions within the population on evolutionary dynamics and its impact on population performance, already discussed in Phillips and Wolfe (2005). On this subject, Döring et al (2011) raised three points: (a) the evolutionary advantage of genotypes producing more and smaller kernels over those producing less and larger kernels, (b) a possible population drift towards the prevalence of highly competitive, but agronomically poor genotypes, as already pointed out by Murphy et al (1982), and (c) a possible trade-off between yield increase and end-use quality, e.g. grain protein content.…”
Section: Functional Genetic Diversity In a Dynamic Perspectivementioning
confidence: 98%
“…the ability to exactly predict the identity of the material that we are growing. Murphy et al (1982) addressed the problem of the compositional stability of multiline cultivars, trying to understand whether these seeds would better be considered as cultivars or blends. Multilines are basically mixtures of near-isogenic, bulk-reproduced lines.…”
Section: Identity and Heterogeneity Of The Seedsmentioning
confidence: 99%
“…In all cases the best available copy has been filmed. Murphy et al (1982) reported that the isoline composition of a multiline variety of oats did not remain con stant over a four-year period that the multiline was propa gated. The composition changed similarly and significantly when the multiline was grown in a rust-free and in a rustepidemic environment, so the authors concluded that the isolines possessed differing competitive abilities that might be related to expression of certain agronomic trait(s).…”
Section: Information To Usersmentioning
confidence: 99%
“…The composition changed similarly and significantly when the multiline was grown in a rust-free and in a rustepidemic environment, so the authors concluded that the isolines possessed differing competitive abilities that might be related to expression of certain agronomic trait(s). As a follow-up to this study, I conducted experiments (a) to de termine whether differing competitive abilities could be measured among the isolines used in the Murphy et al (1982) study, among oat isolines in the Multiline E series (Frey and Browning, 1976b), among five oat varieties, and among oat and barley varieties and (b) to assess whether specific agronomic traits could be associated with differences in competitive ability.…”
Section: Information To Usersmentioning
confidence: 99%